Development of models for forecasting of seasonal ground level ozone (O3) - Napi N.N.L.M.; Abdullah S.; Mansor A.A.; Ahmed A.N.; Ismail M. (Taylor's University, 2023)
Ozone (O3) is a secondary pollutant that releases to the atmosphere through industrial and motor vehicles emission which give an adverse impact, especially on human health. The meteorological factor especially weather condition has influenced the production of O3 concentration in the atmosphere. This study aims to develop O3 forecasting model during different monsoon seasons. The data from the year 2012 until 2014 were acquired including O3, nitrogen oxide (NO), nitrogen dioxide (NO2), carbon monoxide (CO), sulphur dioxide (SO2), wind speed (WS), ambient temperature (T) and relative humidity (RH) on an hourly basis. The Multiple Linear Regression (MLR) models were developed for the prediction of up to 3 hours in advance. Southwest Monsoon (SWM) was having a higher O3 concentration with a mean value of 0.024 ppm while Inter Monsoon 2 (IM2) was having the lowest concentration of O3, 0.019 ppm. The best fits MLR models for each monsoon were O3,t+1 as compared to O3,t+2 and O3,t+3. The better interpretation and prediction of O3 behaviour during monsoon conditions can help the responsible parties to plan early mitigation measures to address the air pollution problem. School of Engineering, Taylors University.